EVALUASI SPT TAHUNAN ELEKTRONIK - Kasim, Elsie Sylviana; Nur, Titin Fachriah (UI Scholars Hub, 2016)
Evaluation of services of Electronic Annual Tax Return is conducted to determine the quality of services of Electronic Annual Tax Return. This is done by using the five Service Quality (SERVQUAL) dimensions which are tangibles, realibility, responsiveness, assurance and empathy. The result of the research and analysis of Evaluation of services of Electronic Annual Tax Return concluded that Taxpayers are satisfied with the quality of Electronic Annual Tax Return. Advices given to the djponline.pajak.go.id websites is it should be more attentive to the needs of the Taxpayers. Djponline.pajak.go.id websites should not only pay attention to the functions but also increased trust amoung Taxpayers toward djponline.pajak.go.id websites.